Peran Citra Merek, Harga Dan Kemasan terhadap Keputusan Pembelian Air Minum Dalam Kemasan Aqua - Rizal Maulana Ismuputro (Jurnal Ilmu Manajemen, 2020)
Various water products include packaging made for customers needed, one of them is an Aqua. Aqua is the main drinking product from PT. Aqua Golden Mississipi. According to Top Brand Index in 2017 until 2019, Aqua can be a brand leader of bottled water producers. This research aims to discuss images of the brand, price, and packaging for drinking water purchasing decisions of Aqua in Surabaya. The data of the study were analyzed using multiple linear regression techniques. The result out of research shows that the effects of brand image on purchase decisions but the packaging variable will not influence the purchase decision. In this research dominated effect is the variable brand image.